Comparative analysis of ICSI outcomes with testicular or secondary ejaculated sperm in men with oligoasthenoteratozoospermia - Marzieh Derakhshan; Mahsa Foroughi; Ensieh Salehi; Elham Naghshineh; Hatav Ghasemi Tehrani; Maryam Derakhshan; Atefeh Bamarinejad (Middle East Fertility Society Journal)
Abstract Objective To investigate the comparative outcomes of intracytoplasmic sperm injection (ICSI) using sperm from testicular biopsies versus secondary ejaculated sperm in men with oligoasthenoteratozoospermia (OAT), aiming to identify optimal strategies for improving fertility success rates. Methods This prospective study involved 36 infertile men with OAT undergoing ICSI treatment. On the day of oocyte retrieval, a semen sample through short-interval secondary ejaculation was obtained from each patient and also they underwent testicular sperm retrieval using fine needle aspiration (FNA). Sibling MII oocytes were randomly allocated to two groups: those injected with sperm from secondary ejaculation and those injected with testicular sperm from FNA. Embryo quality, fertilization rates, and blastocyst formation rates were compared as primary outcomes of the study. Results A total of 42 participants were enrolled, with 36 completing the analysis. The second ejaculation showed significantly enhanced progressive sperm motility and lower sperm DNA fragmentation compared to the first. ICSI outcomes revealed no significant differences in fertilization rate (76.48% vs. 75.17%, P = 0.46), blastocyst formation rate (57.50% vs. 57.86%, P = 0.65), and cleavage rate (85.18% vs. 86.81%, P = 0.31) between secondary ejaculation and FNA groups. High-quality embryos were slightly more in the secondary ejaculation group (2.61 ± 1.61 vs. 2.47 ± 1.56, P = 0.06). Conclusions While testicular sperm retrieval via FNA has been a standard approach in ICSI for men with OAT, secondary ejaculation presents a valuable alternative that can achieve comparable embryological outcomes. This approach could be a less stressful and equally effective option for OAT patients who prefer less invasive procedures, potentially enhancing reproductive success in men with OAT. Further studies with larger sample sizes that investigate clinical pregnancy and live birth rates are needed to confirm these findings and address our limitations.